Impact of Socio-Demographic Factors on Different Personality Types in Individuals - Hira Butt, Nauman Rauf Khan, Saeed Ur Rehman, Rizwana Sultan, Zainab Waheed, Khadija Amjad (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To assess the impact of socio-demographic factors on different personality types in individual. Methodology: A Cross-sectional descriptive study was conducted in College of Dentistry, Sharif Medical and Dental College, Lahore over a period of 5 months from July to November 2021. Data was collected using a ten-item personality inventory scale (TIPI). The sociodemographic variables included age, gender, marital status, occupation and educational level. All individuals irrespective of their age and gender were included in the study. Individuals with a history of psychiatric illness were excluded from the study. Results: There was a statistically significant difference in conscientiousness personality traits among age groups (p=0.006). Similarly, the difference in the personality trait of agreeableness (p≤0.001), conscientiousness (=0.016), and emotional stability (p=0.007) across gender was statistically significant. There was also a statistically significant difference in the scores of agreeableness among the employed and unemployed individuals (p=0.044). Conclusion: The conscientiousness personality trait score among age groups was the highest for the age group 50 to 59. The personality trait scores of agreeableness, conscientiousness, emotional stability across gender were higher in females in comparison to males. The contrary was true for emotional stability. The score of agreeableness was higher for unemployed individuals in comparison to employed individuals.